The dual role of microglia in ischemic stroke and its modulation via extracellular vesicles and stem cells - Matteo Haupt; Stefan T. Gerner; Thorsten R. Doeppner (Neuroprotection)
Abstract Stem cell‐based therapies and extracellular vesicle (EV) treatment have demonstrated significant potential for neuroprotection against ischemic stroke. Although the neuroprotective mechanisms are not yet fully understood, targeting microglia is central to promoting neuroprotection. Microglia are the resident immune cells of the central nervous system. These cells are crucial in the pathogenesis of ischemic stroke. They respond rapidly to the site of injury by releasing pro‐inflammatory cytokines, phagocytizing dead cells and debris, and recruiting peripheral immune cells to the ischemic area. Although these responses are essential for clearing damage and initiating tissue repair, excessive or prolonged microglial activation can exacerbate brain injury, leading to secondary neuroinflammation and neurodegeneration. Moreover, microglia exhibit a dynamic range of activation states with the so‐called M1 pro‐inflammatory and M2 anti‐inflammatory phenotypes, representing the two ends of the spectrum. The delivery of both EVs and stem cells modulates microglial activation, suppressing pro‐inflammatory genes, influencing the expression of transcription factors, and altering receptor expression, ultimately contributing to neuroprotection. These findings underscore the importance of understanding the complex and dynamic role of microglia in the development of effective neuroprotective strategies to reduce the effects of ischemic stroke. In this review, we examine the current state of knowledge regarding the role of microglia in ischemic stroke, including their molecular and cellular mechanisms, activation states, and interactions with other cells. We also discuss the multifaceted contributions of microglia to stem cell‐ and EV‐based neuroprotection during an ischemic stroke to provide a comprehensive understanding of microglial functions and their potential implications in stroke therapies.